LSST survey: millions and millions of quasars. Issue Volume 12:Issue S324(2016) (23rd June 2017) - Ivezić, Željko
Abstract: The Large Synoptic Survey Telescope (LSST), the next-generation optical imaging survey sited at Cerro Pachon in Chile, will provide hundreds of detections for a sample of more than ten million quasars with redshifts up to about seven. The LSST design, with an 8.4m (6.7m effective) primary mirror, a 9.6 sq. deg. field of view, and a 3.2 Gigapixel camera, will allow about 10, 000 sq. deg. of sky to be covered twice per night, every three to four nights on average, with typical 5-sigma depth for point sources of r =24.5 (AB). With about 1000 observations in ugrizy bands over a 10-year period, these data will enable a deep stack reaching r =27.5 (about 5 magnitudes deeper than SDSS) and faint time-domain astronomy. The measured properties of newly discovered and known astrometric and photometric transients will be publicly reported within 60 sec after closing the shutter. In addition to a brief introduction to LSST, I review optical quasar selection techniques, with emphasis on methods based on colors, variability properties, and astrometric behavior.